Disputes over pastures in the nineteenth-century Balkans. - Öncel, Fatma (Middle Eastern Studies, 2024)
This research aims to contribute to the literature on Ottoman common and by analysing how mid-nineteenth century land codes influenced conflicts regarding common pastures in the Balkans. To accomplish this goal, two sets of primary sources are analysed: legal documents (Land Code of 1858 and Title Deed Regulation of 1859) as well as petition records from the Ottoman Imperial Archives. Case studies of land disputes occurring between commoners and large estate (çiftlik) holders in the Balkans are selected from the years following the enactment of these land codes. This selection enables an examination of the impact of these codes on the arguments presented by the conflicting parties. The central argument of this study points out that the Ottoman Empire's efforts to codify land laws played a crucial role in shaping the disputes over communal pastures. However, it is equally important to underline that these legal changes did not signify an unqualified victory for private property rights over commons. Instead, the rural population countered landholders' efforts by employing petitioning as a proactive strategy.